Research Inventory of Undergraduates at Rundu Campus [A Cross-sectional Exploratory Case Study to Understanding the focus of Research at a University of Namibia Satellite Campus] - Kavei, Gurvy; Karupu, Erwina (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
Since its existence, the Rundu Campus of the University of Namibia hasn’t created a simple and accessible database of undergraduate student research. This is the first cohort to undertake their undergraduate Research in part fulfilment of their course requirements. In subsequent years, this number of students undertaking Research would invariably grow due to the increased enrolment across all three faculties. Taking a longitudinal (2016 – 2021) exploratory content analysis, this research compiled a primary database of research topics (N=256) to understand the areas of research interest students have been focusing on over this period. Over 40% of the Campus research targets students as subjects of research while the campus research is largely interpretative (13.1%), exploratory (13.3%) and seeking to evaluate the knowledge (28%) of students across a large spectrum of health, education, and business-related issues. In the field of academia, it is important to know the different research titles done by the students so they can have an inventory. Also, already researched titles should not be repeated as students and faculty are guided on what research is necessary to be done every year. The study recommends extending future research beyond just the “Research Topics’ to cover a full breadth of Campus research work up to their conclusions and recommendations. Furthermore, the study recommends the Campus academic society do more than merely study “students” and cover broader socio-economic aspects within the Kavango East region for impactful and relevant scholarship. Since the challenges of research mapping are perennial (year-in-year-out), it would be helpful for future researchers to apply different methodologies or approaches like action research which provides an opportunity for observing evolving research dynamics in real time.